Agency and Violence in Frantz Fanon's Psychiatric Writings - Cassatella, Andrea (African studies (Johannesburg), 2025)
The apparent quotidian violence in Africa today is an undeniable reality that raises important questions about its causes, forms and implications for the life and agency of African people and societies. This article proposes to reflect on these questions by exploring Frantz Fanon's recently published psychiatric writings, mostly written in North-Africa, which have sparked important reconsideration of his work as a whole in both Fanonian and critical scholarship. The central suggestion advanced is that these writings offers clinical practice-based theoretical insights that are not simply central to Fanon's revolutionary project of liberation as a whole, but also to the task of critically thinking about violence and agency in the African present. What surfaces from these works is that, while liberation from violence cannot occur without political and material transformations, it also cannot occur unless the psychological dimension is taken seriously, understood, and addressed.